Proceedings of the 2023 CHI Conference on Human Factors in Computing Systems 2023
DOI: 10.1145/3544548.3580969
|View full text |Cite
|
Sign up to set email alerts
|

Choice Over Control: How Users Write with Large Language Models using Diegetic and Non-Diegetic Prompting

Abstract: Figure 1: Overview of our four UI variants, showing the user's written text (black font, i.e. a diegetic prompt), the suggestions (text highlighted in green, and options in the list), and a popup text box that allows users to input an instruction as a zero-shot prompt to the system (i.e. a non-diegetic prompt).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Researchers studied how these LLM suggestions can change people's writing and found that generated texts could spark new ideas [14,18,36], lower grammatical errors [58], and increase vocabulary diversity [58], while introducing cognitive challenge of integrating generated texts into the user's writing [14,90]. Researchers also studied how specific designs of LLM, such as the number of suggestions [13] or allowing users to input instructional prompts or not [25] can impact writing. Moreover, the researchers investigated the sense of ownership of writings with AI suggestions [28].…”
Section: Usingmentioning
confidence: 99%
“…Researchers studied how these LLM suggestions can change people's writing and found that generated texts could spark new ideas [14,18,36], lower grammatical errors [58], and increase vocabulary diversity [58], while introducing cognitive challenge of integrating generated texts into the user's writing [14,90]. Researchers also studied how specific designs of LLM, such as the number of suggestions [13] or allowing users to input instructional prompts or not [25] can impact writing. Moreover, the researchers investigated the sense of ownership of writings with AI suggestions [28].…”
Section: Usingmentioning
confidence: 99%
“…Researchers have been investigating the integration of advanced artificial intelligence technologies to support various tasks. These tasks span a wide spectrum of HCI applications, encompassing question-answering systems [35], story generation [13,15], automatic generation of visualizations [16] and personalized news recommendation [32].…”
Section: Llm-supported Designmentioning
confidence: 99%
“…Specifically, the development of Low-code LLM [10] and PromptCrafter [1] have been dedicated to capturing user intent through well-crafted text prompts and optimizing the wording of prompts. Dang et al [15] integrated a user interface (UI) for phrase suggestions and a UI for zero-shot prompt inputs into an LLM. Our approach integrates the chain-of-thought technique [55] and leverages few-shot examples [7] to enhance the prompt optimization, ultimately aiming for improved and more effective outcomes.…”
Section: Llm-supported Designmentioning
confidence: 99%
“…For instance, Jiang et al [24] introduced PromptMaker, a tool that combines Prefixes, Settings, and Examples to create structured prompt inputs. Similarly, Dang et al [14] developed UI variants that integrate user instructions with the standard prompting, enhancing more nuanced user-model interaction.…”
Section: Mode 2: User Interface (Ui) Uer Interface (Figurementioning
confidence: 99%